Improving Knowledge and Emotion Management Psychology Students through Emotion Stabilization Training - Mardhiyah, Sayang Ajeng; Pratiwi, Marisya; Dwi Iswari, Rosada; Purnamasari, Ayu (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
The purpose of this study is to determine how life design group counseling can improve students' career decision-making skills. This research is a type of action research using the Kemmis and Taggart model. The research was conducted in four stages: planning, action, observation, and reflection. The study involved 10 students from class XII, who were divided into two groups: 5 students in group A and 5 students in group B. Research data were collected through observation, inventory, and interviews. The instruments used included observation guidelines, inventory questionnaires, and interview guidelines. The inventory instrument contained 39 valid items with an alpha Cronbach value of 0.825. The research was conducted in three cycles with quantitative descriptive analysis. The results showed that through life design counseling conducted by implementing questions in career construction interviews and planning goals and efforts in achieving future career goals, students were able to plan their careers carefully despite facing failure. Students also understand their interests and potential as career opportunities. The results of the interview explained that the life design group counseling services provided can improve career decision-making skills so that students do not feel confused. It was proven that 9 out of 10 students were able to identify the chosen further study majors, 3 of them succeeded in entering college without a test. Therefore, it is concluded that life design counseling can help counseling teachers in helping students in making career decisions. It is also suggested to implement life design counseling in other counseling service strategies